RAPID OSCILLATIONS IN THE SPECTRUM OF roAp STARS χ PSC AND γ EQU - Aliev, S. G.; Ismailov, N. Z. (Одеські астрономічні публікації, 2017)
Results of high time and spectral resolution spectral observations with CCD in 1998-1999 for Ap stars χ Psc and γ Equ were presented. Spectroscopic parameters (Vr, Wλ) of spectral lines SiII, CrI, CrII, FeI, FeII, Hα, Hβ shows that despite of different value of rotation velocity of χ Psc (180 km/s) and γ Equ (∼74 years), both stars shows short-time oscillations of spectral parameters, and concern to a subgroup of roAp stars. It is showed that spectroscopic parameters and magnetic field strength variations may be described with short-time pulsation periods ∼17 min and ∼12 min for χ Psc and γ Equ correspondingly.